Promoting Influenza Vaccination Among an ACA Health Plan Subscriber Population: A Randomized Trial. Issue 6 (July 2019) - Nehme, Eileen K.; Delphia, Michelle; Cha, Eun Me; Thomas, Milton; Lakey, David
Purpose: To assess the effectiveness of an intervention to promote influenza vaccination among members of an Affordable Care Act (ACA) insurance plan. Design: Randomized controlled trial. Setting: Messages were delivered by a community-based, nonprofit health insurance provider to its members in Central Texas. Participants: Adult subscribers for whom either a phone number or an e-mail address was available (n = 25 649). Intervention: Participants were randomly assigned to be sent (1) no messages, (2) messages encouraging influenza vaccination via e-mails and texts, and (3) messages encouraging influenza vaccination through e-mails, texts, and postal mail. Messages were sent between September 12, 2017 and November 17, 2017. Measures: Influenza vaccination was determined using medical and pharmacy claims. Analysis: Rate differences and 95% confidence intervals between each exposure condition were calculated for the overall population and by subgroups. Results: The vaccination rate by December 31, 2017 was 16.9%. Those sent both electronic messages and postal mail were significantly more likely to be vaccinated than those who were not sent messages (rate difference: 2.5%; 95% confidence interval [CI]: 1.4-3.6) and those who were sent electronic messages only (rate difference: 1.6%; 95% CI: 0.5-2.8). Conclusion: A combination of messages delivered via text, e-mail, and postal mail generated a modest but significant positive effect on influenza vaccine rates in an ACA plan population. The postal mail component was essential for achieving this effect.